Strategi Peningkatan Kinerja Perawat melalui Support Mental dan Gaya Kepemimpinan Kepala Ruangan yang Dimediasi oleh Psychological Capital : Integrative Review - Zulfi Ekawaty; Ariyanti Saleh; Rini Rachmawaty (Jurnal Kesehatan, 2023)
Background: Psychological capital is a positive capacity possessed by individuals to develop in improving nurse performance. Several studies state that the performance of nurses is still not optimal. Therefore, mental support and leadership style mediated by psychological capital are needed as a strategy to improve nurse performance. Purpose: This review aims to identify literature related to psychological capital, emotional support and leadership style to support the improvement of nurse performance in service. Methods: This study used an integrative approach based on Whittemore and Knaf's use to conduct the review. The articles used are published from 2012 to 2020 using the Proquest, Pubmed, and Science Direct databases. Results: The search returned 15 articles that met the inclusion criteria. Positive psychological capital has a positive relationship to nurse performance. Interventions for nurses to improve performance by increasing positive psychological capital must be developed and made available to nurses. Interventions focused on the individual level excluding the broader social context or organizational level. Conclusion: Positive psychological capital can influence the performance of nurses in providing services to patients. Hospital nursing managers need to provide training to nurses regarding psychological capital to increase their psychological capital.